2008
DOI: 10.1158/0008-5472.can-06-4418
|View full text |Cite
|
Sign up to set email alerts
|

Distinctive MicroRNA Profiles Relating to Patient Survival in Esophageal Squamous Cell Carcinoma

Abstract: Esophageal cancer is the sixth leading cause of death from cancer and one of the least studied cancers worldwide. The global microRNA expression profile of esophageal cancer has not been reported previously. Here, for the first time, we have investigated expressed microRNAs in cryopreserved esophageal cancer tissues using advanced microRNA microarray techniques. Our microarray analyses identified seven microRNAs that could distinguish malignant esophageal cancer lesions from adjacent normal tissues. Some micro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
265
3
4

Year Published

2009
2009
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 313 publications
(281 citation statements)
references
References 48 publications
(52 reference statements)
9
265
3
4
Order By: Relevance
“…17 Several studies have showed that miRNAs might contribute to human carcinogenesis and cancer progression and be considered as potential novel targets for cancer diagnosis and treatment. 2,8 The global miRNA expression profile in ESCC was demonstrated for the first time in 2008, 18 and some miRNAs have been reported to exert regulatory functions in ESCC. miRNAs, including miR-21, miR-31, miR-577, etc, act as oncogenes, [19][20][21] while others such as Let-7, miR-98, miR-100, miR-138, miR-143, miR-150, etc, function as tumor suppressors.…”
Section: Discussionmentioning
confidence: 99%
“…17 Several studies have showed that miRNAs might contribute to human carcinogenesis and cancer progression and be considered as potential novel targets for cancer diagnosis and treatment. 2,8 The global miRNA expression profile in ESCC was demonstrated for the first time in 2008, 18 and some miRNAs have been reported to exert regulatory functions in ESCC. miRNAs, including miR-21, miR-31, miR-577, etc, act as oncogenes, [19][20][21] while others such as Let-7, miR-98, miR-100, miR-138, miR-143, miR-150, etc, function as tumor suppressors.…”
Section: Discussionmentioning
confidence: 99%
“…Procedures were performed as described in Guo et al (2008). microRNAs were isolated from the breast cancer cell lines as well as breast cancer tissues using the miRNeasy Mini Kit (Qiagen, Valencia, CA, USA), according to the manufacturer's protocol.…”
Section: Methodsmentioning
confidence: 99%
“…To date, has-miR-335, has-miR-181d, has-miR-25, has-miR-7, and has-miR-495 have been confirmed correlated with histopathological stages of EC. In addition, abnormal miRNA expression spectra are different between esophageal squamous cell carcinoma (ESCC) tissues and esophageal adenocarcinoma (EAC) tissues (Guo et al, 2008;Mathée et al, 2009).…”
Section: Screening Of Microrna In Patients With Esophageal Cancer At mentioning
confidence: 99%